Profil Stres Kerja Guru Raudhatul Athfal (RA) Terhadap Perubahan Model Pembelajaran Pasca Pandemi Covid-19 - Roby Maiva Putra; Shidratul Attika; Arlizon Raja; Mhd. Abror (TANJAK, 2023)
Work stress is a condition of psychological disorder that is experienced by many individuals in the world of work, including for Guru Raudhatul Athfal, especially in the face of changing workloads during the COVID-19 pandemic. This research uses a descriptive method with a quantitative approach. This method was chosen based on consideration of the research objectives, namely to see the stress profile of Teacher Raudhatul Athfal towards changes in learning models after the COVID-19 pandemic. The population in this study is Guru Raudhatul Athfal in Bintan Regency, Riau Islands Province. The research sample was selected using simple random sampling techniques and obtained a sample of 30 Teachers Raudhatul Athfal. Data collection is done using a research questionnaire whose results are then analyzed using a percentage formula. The results showed that Guru Raudhatul Athfal's stress level was mostly in the low category with a percentage of 76.67%. This means that Guru Raudhatul Athfal has low work stress due to changes in learning models after the COVID-19 pandemic. This should have a positive impact on the commitment and productivity of the Teacher's work.